Teacher Procrastination, Emotions, and Stress: A Qualitative Study - Laybourn, Sara; Frenzel, Anne C.; Fenzl, Thomas (Frontiers in Psychology, 2019)
Stress and negative emotions in teachers can lead to occupational burnout, poor performance in the classroom, and decreased job-satisfaction. Apart from having negative personal and physical effects for the individual teacher, teacher stress and burnout are also thought to have negative effects on the respective students and student achievement. As one potential source of teacher stress, procrastination has been speculated about. However, research on the phenomenology and prevalence of procrastination among teachers, as well as its relevance for their emotional and stress experiences, is very scarce. Further, most of the existing research on teacher procrastination used general self-report scales to obtain results. The present study therefore investigated the phenomenology of teacher procrastination as well as its links with emotional experiences and stress, using a qualitative approach. Twenty-seven male and female teachers from Germany were interviewed personally (Mean age = 35.7, SD = 9.64, Min = 25 years, Max = 67 years). Nine of those teachers reported to never needlessly delay an action concerning their profession or not to perceive their dilatory behavior as negative and stressful. Data from the remaining 16 teachers (Mean age = 35.06, SD = 7.0, Min = 26 years, Max = 48 years) were analyzed on the basis of qualitative content analysis by using deductive as well as inductive category application. Results revealed that these teachers procrastinate on an array of professional tasks, such as administrative and organizational tasks, correcting students’ work, and evaluating students on their general work and performance. The results showed that teachers delayed these tasks for different reasons but mainly due to task aversiveness. Further, teachers reported experiencing mainly negative emotions when procrastinating and perceiving their procrastination behavior as moderately stressful, indicating that procrastination is a further stressor in the teacher profession. Limitations of the study are discussed and directions for future research are proposed.